Mathematical Theory of Feynman Path Integrals : an introduction - Albeverio, Sergio A. (Springer, 2017)
The Fresnel Integral of Functions on a Separable Real -- The Feynman Path Integral in Potential Scattering -- The Fresnel Integral Relative to a Non-singular Quadratic Form...